O uso de imagens de satélite no ensino de geografia: possibilidades e limitações na educação básica - Silva Filho, Israel da (2008)
This work is done to analyze and put in evidence some pedagogical procedures that can show us possibilities and limitations about using satellite images when teaching geography. It s so easy to find satellite images because they are all over the Internet sites but they haven t been used adequately by geography teachers because they don t know how to use it in order do make it easier for their students understand the space organization that they have to study. Besides, we think it s so important to discuss some questions related to pedagogical procedures, politics and economics that show us how the places can be so diverse when we are talking about new technology for teaching. In this case we have to consider the difficulty in accessing the internet, a poor structure in a public school, an over value attributed to new technology or even a refuse without any reasons, and the difficulty of working with this kind of resources. As satellites images are specific when compared with other traditional ways used to for teaching geography, we tried to show their specificity when we did and developed two activities students that are doing the seventh level of elementary school. At this time, that king of materials was used to show some aspects of the space that are impossible of been saw when we are using traditional ways of teaching. Then we tried to put in evidence that teachers have to be careful when using satellite images because they must use them connected with their pedagogical purposes which main subject is to prepare the students to read, to interpret and to transform their reality